2020
DOI: 10.1080/10942912.2020.1823409
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of functional low-fat yogurt enriched with whey protein concentrate, Ca-caseinate and spirulina

Abstract: Fresh buffalo milk was standardized to 1.2 g fat 100 g −1 milk. Low-fat, yogurts were fortified with whey protein concentrates (WPCs) 1 g 100 g −1 , Cacaseinates (Ca-Cns) 1 g 100 g −1 , and spirulina (Spirulina platensis) 1 g 100 g −1 powders and their potential effect on the different quality characteristics were studied. Total solids, ash, and fat contents were high in low-fat yogurt added with spirulina powder, while protein content was high in lowfat yogurt enriched with WPCs. The highest level of antioxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 41 publications
(58 reference statements)
1
16
1
1
Order By: Relevance
“…The increase in total antioxidant activity in Spirulinafortified yogurt can be ascribed to the antioxidant activity of Spirulina. Similar to those detected by Atallah et al [35], reporting the most outstanding value of antioxidant activity corresponding to low-fat yogurt fortified with Spirulina. The increase in free radical scavenging may be due to the high carotenoids, chlorophylls and phycocyanin in Spirulina powder [36].…”
Section: Discussionsupporting
confidence: 89%
“…The increase in total antioxidant activity in Spirulinafortified yogurt can be ascribed to the antioxidant activity of Spirulina. Similar to those detected by Atallah et al [35], reporting the most outstanding value of antioxidant activity corresponding to low-fat yogurt fortified with Spirulina. The increase in free radical scavenging may be due to the high carotenoids, chlorophylls and phycocyanin in Spirulina powder [36].…”
Section: Discussionsupporting
confidence: 89%
“…This behavior was expected, since A. platensis has a high protein content (around 70% in many cases [ 18 , 19 ]). Specifically, in the studies developed by Atallah et al [ 50 ] it was observed that the protein values were 5.4% for the control sample and 6.2% for the yogurt fortified with 1% A. platensis added before the fermentation process. Similar results were reported by Silva et al [ 51 ] in yogurts with A. platensis added after the fermentation process.…”
Section: Applications Of Microalgal Biomass and Its Derivatives In Yo...mentioning
confidence: 99%
“…Silva et al [ 51 ] observed that the antioxidant capacity increased by 150% in yogurts fortified with 1% A. platensis , when compared to the control (yogurt without microalgae addition). Likewise, Atallah et al [ 50 ] and Alizadeh et al [ 57 ] also studied the antioxidant activity of yogurt enriched with 1.0 and 0.5% A. platensis powder and observed a sharp rise in the antioxidant activity corresponding to 200.02% and 110.88% for each treatment. This results from the presence of chlorophyll, carotenoids, and phycocyanin in A. platensis biomass, the release of which can be increased by the interaction with the lactic acid bacteria present in the fermented dairy.…”
Section: Applications Of Microalgal Biomass and Its Derivatives In Yo...mentioning
confidence: 99%
See 2 more Smart Citations